EVALUASI PROGRAM BK DI SEKOLAH - Indiati, Indiati (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2011)
BK program evaluation in schools is an attempt to get various information on a regular basis, continuous and thorough about the process and outcome of the development of attitudes and behavior, or developmental tasks the students through a program of activities that have been implemented. Assessment activities in school guidance and counseling was intended to determine the degree of quality improvement activities related to implementation of guidance programs in schools with reference to the criteria or standards specified in accordance with the guidance program implemented.Criteria or benchmarks used to assess the success of program implementation guidance and counseling services in schools is referring to are met or not met the needs of students and the parties involved either directly or indirectly contribute to help students gain and behavior change toward more personal good.